Strategies support for school learning and study in parents of high perfomance students - Bazán-Ramírez, Aldo; Navarro-Romero, Ana L.; Treviño-Siller, Sandra; Castellanos-Simons, Doris (Profesorado, Revista de Currículum y Formación del Profesorado, 2014)
Introduction: Several studies have explored whether family support given to children influences in better academic performance and contributes to the formation of appropriate study habits that improves future academic development. Some studies have argued that school programs aiming at involving parents, are the ones that achieve greater success; others argue that the voluntary support of parents ,the family group or the close social network are essential in order to generate the gradual development of habits and academic strengths in children. Design and method: Qualitative, exploratory and cross sectional research in five schools of different socio-cultural and socio-economic contexts in the State of Morelos, Mexico to identify the strategies that parents develop to support their children in their academic performance. Information was collected by means of five focus groups with a specific guide designed for this study. Content analysis permitted to identify recurrences and differences in parents´answers Results: Parents are not aware that they develop strategies to support their childrens´academic performance. They explained high performance due to personal characteristics and abilities of their children. The strategies identified by the research team include establishing routines,continuous monitoring of children, time spent, enabling appropriate spaces for the study, constant communication and seeking support with other social actors when parents feel that they do not have the necessary knowledge to support. Conclusions: Since parents are not aware of their role as agents of support, it becomes necessary to sensitize and inform other parents about strategies that may help their children in order to improve academic performance (workshops). Besides, it is recommendable to replicate this study in other regions of the country and to explore with parents of children who are not successful at school and therefore to identify if any kind of support strategies are developed, as well as the reasons.